2014
DOI: 10.1371/journal.pone.0089229
|View full text |Cite
|
Sign up to set email alerts
|

Central Proliferation and Neurogenesis Is Impaired in Type 2 Diabetes and Prediabetes Animal Models

Abstract: Type 2 diabetes (T2D) is an important risk factor to suffer dementia, including Alzheimer’s disease (AD), and some neuropathological features observed in dementia could be mediated by T2D metabolic alterations. Since brain atrophy and impaired neurogenesis have been observed both T2D and AD we analyzed central nervous system (CNS) morphological alterations in the db/db mice (leptin receptor KO mice), as a model of long-term insulin resistance and T2D, and in C57Bl6 mice fed with high fat diet (HFD), as a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 50 publications
6
62
0
Order By: Relevance
“…As for the role of hyperglycemia in neurogenesis, some studies indicate that long-term hyperglycemia suppresses proliferation of hippocampus NSPCs using streptozotocin-(STZ) induced type 1 diabetes model (Jackson-Guilford et al, 2000;Saravia et al, 2004;Beauquis et al, 2006;Zhang et al, 2008;Guo et al, 2010) or spontaneous type 1 diabetes model (Beauquis et al, 2008;Guo et al, 2010), while other researches find an enhanced proliferation of NSPCs employing type 2 diabetes model (Lang et al, 2009;Ramos-Rodriguez et al, 2014). The discrepancy among studies may be attributed to different hyperglycemic models and target blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the role of hyperglycemia in neurogenesis, some studies indicate that long-term hyperglycemia suppresses proliferation of hippocampus NSPCs using streptozotocin-(STZ) induced type 1 diabetes model (Jackson-Guilford et al, 2000;Saravia et al, 2004;Beauquis et al, 2006;Zhang et al, 2008;Guo et al, 2010) or spontaneous type 1 diabetes model (Beauquis et al, 2008;Guo et al, 2010), while other researches find an enhanced proliferation of NSPCs employing type 2 diabetes model (Lang et al, 2009;Ramos-Rodriguez et al, 2014). The discrepancy among studies may be attributed to different hyperglycemic models and target blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroscience 303 (2015) 138-148 reduced in type 1 and type 2 diabetic models (JacksonGuilford et al, 2000;Beauquis et al, 2006Beauquis et al, , 2008Zhang et al, 2008;Lang et al, 2009;Ramos-Rodriguez et al, 2014), which suggested a potential role of blood glucose in self-renewal and proliferation of NSPCs.…”
Section: Introductionmentioning
confidence: 99%
“…HFD was previously shown to induce a remarkable brain insulin resistance as well as spatial memory impairment in a normal mouse or a transgenic model of AD [25]. However, whether the state of hyperinsulinemia in rodents can induce alterations in the central nervous system (CNS) remains controversial and observations seem to depend on the experimental approach to induce hyperinsulinemia and the specific tests performed [26][27][28][29]. Therefore this study was undertaken in an attempt to understand the underlying mechanisms by which adipose tissue might influence cerebral structures related to learning and memory.…”
Section: Please Provide Corresponding Author(s) Photographmentioning
confidence: 99%
“…Such weakening can be provoked by the central leptin deficiency, the altered activity of leptin receptor and IRS-proteins, and the decreased response of hypothalamic neurons to insulin [175,176]. It was shown that the leptin deficiency and the leptin resistance in the CNS were involved in the impairment of cognitive functions in T2DM, MS and also in experimental type 1 DM [171,174,177,178]. Since leptin stimulates the transcription of genes encoding IR and IRS-proteins, a decrease of its regulatory effects at the early stages of insulin resistance leads to weakening of function of the brain insulin system and exacerbates insulin resistance.…”
Section: Leptin Signaling Systemmentioning
confidence: 99%
“…This is due to the development of leptin resistance, a decrease of the level of endogenous leptin, and inefficiency of leptin therapy in the case of the central leptin signaling being impaired [171,179]. In some cases the replacement therapy with leptin is effective.…”
Section: Leptin Signaling Systemmentioning
confidence: 99%